PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN DND PET TERHADAP KEPUASAN KONSUMEN - Edwin Soekotjo (Jurnal Performa)
The purpose of this research is to find out the influence of product quality and service quality of Dnd Pet on customer satisfaction. The variables that are done in this research are product quality and service quality variables as independent variables and consumer satisfaction as dependent variable. The method in this research is quantitative data analysis method with SPSS. The sample of this research is consumers who have purchased more than twice at Dnd Pet (Shopee) with the number of 246 people. The method that is used in sampling in this research is probability sampling with data collection using a questionnaire that is distributed using Google Form with Likert Scale. Based on the result of the analysis that has been done, it is known that product quality and service quality variables have significant influence on customer satisfaction.